Twenty four year time trends in fats and cholesterol intake by adolescents. Warsaw Adolescents Study - Charzewska, Jadwiga; Chwojnowska, Zofia; Wajszczyk, Bożena; Chabros, Elżbieta (Anthropological Review, 2015)
The objective of this study was to determine time trends ( 1982–2006) in total fat intake and changes in fatty acid structure intake in adolescents from Warsaw in view of increasing prevalence of obesity. Data come from four successive surveys randomly selected samples of adolescents (aged 11–15 years old), from Warsaw region. In total 9747 pupils have been examined, with response rate varying from 55% to 87% depending on year. Surveys were done always in the spring season of the year. Food intake was assessed by using 24 hours recall method of consumption by the pupils all products, including enriched, dishes and beverages as well as diet supplements, in the last 24 hours preceding the examination. The content of energy and nutrients was calculated by means of own computer softwares (DIET 2 and 4), taking into account successive revisions of the tables of food composition and nutritional values, as well as current Polish DRI. A significant decreasing trend was found in intake of total fat, of saturated fatty acids (SFA) and cholesterol. The percentage of energy from total fat, also decreased both in boys (to 35,1%) and girls (to 33,7%), what failed to reach the desired level below 30% of energy from fat which is recommended. Also significant decrease of SFA consumption was not satisfactory enough to approach the values <10% of energy recommended as was from 13% to 15%. Decreasing trends in fat intake was not in accordance with the trend in obesity prevalence in the adolescents as average BMI is going up. To stabilize the health-oriented changes especially in the diets of adolescents, further activity is desired from professionals working with prevention of adolescents obesity.